2007
DOI: 10.1128/jvi.02754-06
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection of Langerhans Cell Precursors as a Mechanism of Oral Epithelial Entry, Persistence, and Reactivation

Abstract: Epstein-Barr virus (EBV) is a ubiquitous human herpesvirus associated with many malignant and nonmalignant human diseases. Life-long latent EBV persistence occurs in blood-borne B lymphocytes, while EBV intermittently productively replicates in mucosal epithelia. Although several models have previously been proposed, the mechanism of EBV transition between these two reservoirs of infection has not been determined. In this study, we present the first evidence demonstrating that EBV latently infects a unique sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 55 publications
0
39
1
1
Order By: Relevance
“…It has been reported that EBV infects subclasses of DCs, such as skin resident Langerhans cells and follicular DCs (20,21,23). However, although we detected the presence of a viral genome in EBV-treated pDCs, we did not obtain convincing results supporting the ability of EBV to establish infection in these cells.…”
Section: Tlr7/9 Inhibitors Do Not Interfere With Ebv-induced Maturaticontrasting
confidence: 56%
See 1 more Smart Citation
“…It has been reported that EBV infects subclasses of DCs, such as skin resident Langerhans cells and follicular DCs (20,21,23). However, although we detected the presence of a viral genome in EBV-treated pDCs, we did not obtain convincing results supporting the ability of EBV to establish infection in these cells.…”
Section: Tlr7/9 Inhibitors Do Not Interfere With Ebv-induced Maturaticontrasting
confidence: 56%
“…First, it was demonstrated that EBV has the capacity to infect monocytes and DCs (2,(19)(20)(21)(22)(23). In addition, infection of monocytes by EBV was reported to inhibit their development into DCs (24), a process that may affect normal regulation of EBV-host interactions because DCs are known to play a crucial role in the induction of primary T cell response against viruses, including EBV (25,26).…”
mentioning
confidence: 99%
“…For example, EBV infects pre-Langerhans cells in the peripheral blood. 16 However, we did not detect EBV DNA in pre-Langerhans cells (CD1a Ï© CD11c Ï© , and CD14 ÏȘ ) or in basophils (CD123 Ï© ) in PBMCs from 4 patients who had EBV in non-B, non-T, non-monocyte cells (patients 12, 15, 16, and 20), using Immuno-FISH (data not shown). Infection of non-B, non-T, non-monocyte cells may be more common in immunocompromised persons.…”
Section: Ebv In B and Non-b Cells In Blood With Immuno-fish 4555mentioning
confidence: 74%
“…2,[7][8][9][10][11] However, EBV can infect cells other than B cells, including T cells, natural killer (NK) cells, monocytes, and pre-Langerhans cells. [12][13][14][15][16] Several techniques have been developed to detect EBV in cells. In situ hybridization using a probe that detects the EBV-encoded RNAs (EBERs) is considered the best test for localizing latent EBV in tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of suprabasal cells where UPR is activated likely would preclude the establishment of a persistent latent infection and instead would result in productive infection. This situation could arise as an artifact of our system in which the virus might not access the basal surface efficiently or result from the lack of other cell types that might play a role in infection from the basal surface (42,43). Alternatively, a receptor or coreceptor might be expressed more efficiently on differentiated cells; although some investigators observe increased infection in more differentiated keratinocytes (9), others do not (8).…”
Section: Discussionmentioning
confidence: 99%